Kajian Kriteria Penentuan Tempat Istirahat Bagi Pengemud Angkutan Barang di Pantura Koridor Jakarta - Cirebon - Setyabudi, Besar (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Every day the traffic flows along the coast of Jakarta - Cirebon dominating by the transport 1 goods either from the east (Central Java and EastJava) and west (Jakart and Banten). Monitoring results from the path of Jakarta to Cirebon coast showe that many trailer trucks and other freight vehicles crowd along northern route toward JakartCi Cirebon for average speed of about 30-40 miles per hour. The heavs traff1 caused, congestion in a number of points, because of the markets, publ1 transport indiscipline, road conditions and narrowing had because of the curve road and bridg The most important problem is the locations used as temporary pemberhetian place /parkin lot side of the road freight transport mainly Pan tura Jakarta - Cirebon among anillegal dismissal or parked alongside a road leading to, among others, the occurrenc of congestion. To answer the above problems the study was conducted with the approach cualitatif an cuantitatif to look at the reality of (existing) conditions the patter operations and transportation services, by taking a survey between Jakarta - Cirebon,and r search results will be a recommendation of the leadership or policy-making ins ti tu tio1 for transportation of goods in the territory of the North Coast (Pantura) with a condition th should be based on laws and regulations concerning road infrastructure.Keywords: Rest Area, Transport of Goods, Northern Coast-Road of Jakarta-Cirebon